Preparation of RE-containing magnesium alloys via molten-salt-mediated magnesiothermic reduction - Zhimin Zhang; Xuchen Lu; Yan Yan (Journal of Magnesium and Alloys, 2023)
RE-containing magnesium alloys were prepared via molten-salt-mediated magnesiothermic reduction by using RE2O3 (RE=Y, Nd and Gd) and Mg metal as raw materials. The thermomechanical analysis of the magnesiothermic reduction reactions in molten salt was investigated. Then the molten-salt-mediated magnesiothermic reduction process was studied from three different perspectives. After that, the RE-containing magnesium alloy was characterized by using chemical analysis, XRD analysis and SEM analysis. The magnesiothermic reduction was a liquid-liquid reaction with relatively weak driving force. During the melting process and the magnesiothermic reduction process, magnesium metal and the obtained alloy went up and down as a whole in molten salt, which improved the process safety without introducing chloride inclusions. Meanwhile, the hydrolysis of the RECl3-containing molten salt occurred at elevated temperature, which severely impeded the magnesiothermic reduction process. After the magnesiothermic reduction at 750 °C for 2.0 h, the content of RE and the common impurity elements in the obtained RE-containing alloy met the both requirements of the commercial WE43A and WE43B.